2004
DOI: 10.1021/jp035885q
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Studies on the Condensation Coefficient of Water

Abstract: Molecular dynamics (MD) simulations are carried out for water using two kinds of intermolecular potentials, the Carravetta−Clementi (C−C) model and the extended simple point charge (SPC/E) model, to understand the mechanism of interface mass transfer between liquid and vapor. Effects of different interface structures on the condensation process are investigated, and computational data on the condensation coefficient are presented. By changing incident conditions such as the translational and rotational energie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
83
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(107 citation statements)
references
References 36 publications
21
83
0
3
Order By: Relevance
“…The present formulation ensures that ∂K c /∂T K < 0, in accordance with experimental and theoretical studies (Tsuruta and Nagayama, 2004;Kon et al, 2014). Mathematically this present formulation of K c largely eliminates model instabilities by suppressing condensation relative to evaporation throughout the experiment and will be discussed in greater detail in a later section.…”
Section: Thermophysical Properties Of Water Vapor and Moist Airsupporting
confidence: 67%
“…The present formulation ensures that ∂K c /∂T K < 0, in accordance with experimental and theoretical studies (Tsuruta and Nagayama, 2004;Kon et al, 2014). Mathematically this present formulation of K c largely eliminates model instabilities by suppressing condensation relative to evaporation throughout the experiment and will be discussed in greater detail in a later section.…”
Section: Thermophysical Properties Of Water Vapor and Moist Airsupporting
confidence: 67%
“…More recent experiments, for temperatures between 238 and 298 K, have reduced the range to 0.01-1 (Beloded et al 1989;Hagen et al 1989;Shaw and Lamb 1999;Zagaynov et al 2000;Davidovits et al 2006), and Marek and Straub (2001) suggested that condensation coefficients less than 0.01 indicate contamination of the water surface. Molecular dynamics studies, for temperatures between 300 and 350 K, find the value of q c is close to unity (Morita et al 2004;Tsuruta and Nagayama 2004;Vieceli and Tobias 2004), a result that is at odds with many experiments. The reported values of q e also range from 0.01 to 1 (Eames et al 1997), and experimental challenges associated with determining q e again include surface contamination as well as accurate surface temperature measurements (Hickman 1965(Hickman , 1966.…”
Section: Droplet Growth Lawsmentioning
confidence: 99%
“…При этом существует два различных подхода к построению мо-делей -кинетическая многослойная модель (kinetic multilayer model for gas-particle (KM-GAP)) [30] и мо-дель симуляции молекулярной динамики (molecular dynamics (MD) simulations) [31,32]. Модель MD рабо-тает на специальной платформе компьютерного рас-чёта GROMACS с дополнительной надстройкой для расчёта абсорбции жидкими аэрозолями TIP4P-Ew.…”
Section: Hno H O H Nounclassified